2017
DOI: 10.1007/s11239-017-1491-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between TLR9 rs5743836 polymorphism and risk of recurrent venous thromboembolism

Abstract: Recent gene knockout studies on mice have shown the role of toll-like receptor 9 (TLR9) in resolution of venous thromboembolism (VTE) through sterile inflammation. However, the role of a putative functional TLR9 polymorphism (rs5743836) in risk assessment of VTE recurrence remains unknown. The aim of our study was to investigate the TLR9 rs5743836 polymorphism in VTE patients and its association with the risk of VTE recurrence. We analyzed TLR9 rs5743836 polymorphism in Malmö thrombophilia study patients; a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Furthermore, sex differences associated with TLR9 and TLR8 polymorphisms have also been described in CVDs. In whole blood of aging patients with venous thromboembolism, it was observed an association between the TLR9 rs5743836 polymorphism and the risk of venous thromboembolism recurrence in aged women; however, this association was not observed in aged men ( Ahmad et al, 2017 ). Moreover, in whole blood of aging patients with ischemic stroke, it was observed that the TLR8 rs3764880 polymorphism is associated with the susceptibility to ischemic stroke in aging men.…”
Section: Toll-like Receptors Sex Differences and Cardiovascular Agingmentioning
confidence: 94%
“…Furthermore, sex differences associated with TLR9 and TLR8 polymorphisms have also been described in CVDs. In whole blood of aging patients with venous thromboembolism, it was observed an association between the TLR9 rs5743836 polymorphism and the risk of venous thromboembolism recurrence in aged women; however, this association was not observed in aged men ( Ahmad et al, 2017 ). Moreover, in whole blood of aging patients with ischemic stroke, it was observed that the TLR8 rs3764880 polymorphism is associated with the susceptibility to ischemic stroke in aging men.…”
Section: Toll-like Receptors Sex Differences and Cardiovascular Agingmentioning
confidence: 94%
“…NET-related extracellular DNA is recognized by the toll-like receptor 9 (TLR9) on both monocytes and PMNs [ 99 , 100 ], and a mutation in this receptor has been linked to VTE in patients [ 101 , 102 ]. TLR9 −/− mouse VT models have demonstrated larger VT, decreased collagen and fibrin deposition, and an increase in PMNs at 2 days and Mo/MΦ cells after 1 week [ 103 ].…”
Section: Neutrophils and Early Thrombogenesismentioning
confidence: 99%
“…NET-related extracellular DNA is recognized by the toll-like receptor 9 (TLR9) on both monocytes and PMNs, [72,73] and a mutation in this receptor has been linked to VTE in human patients [74,75]. TLR9 -/mouse VT models have demonstrated a consistent pattern of enlarged thrombus, reductions in collagen and fibrin deposition, and a dramatic increase in PMNs at 2 days and Mo/MΦ cells after 1 week [76].…”
Section: Neutrophils and The Potential Regulation Of Early Structuralmentioning
confidence: 99%